Chosen social life quality determinants of 50-year-old female Poles in relation to their health status - Synowiec-Piłat, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2010)
Nowadays, the quality of life has become one of the essential issues that come up when the health status of particular categories or social groups are discussed. It has been empirically proved that not only the biological structure of an organism influences our health, but also that, at a great range, our health is contingent by factors of psychosocial nature. Objectives: The objective of research, performed in April 2009, was to recognize chosen social life quality determinants in a group of mature women, in relation to their health status. Materials and Methods: 209 women – citizens of Wroclaw, aged between 50 and 60, were researched. The assessment was done by means of a highly standardized survey questionnaire. Results: both material and occupational status of most respondents might be regarded as good. It is worth mentioning that, in the opinion of more than half (57%) women researched, their occupation has a negative influence on their health, although to a various degree. Generally, women in the examined group tend to relax in a passive way. What seems advantageous, it is the length and quality of their night dreaming. Only 1/3 of the researched evaluate their condition positively; 44% of them feel various disorders, causing discomfort, once a time, and 14% claim to feel so bad that their health condition makes their normal functioning hard. As many as 72% of these women do not suffer from any terminal illness.